PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X IPA PADA MATERI STRUKTUR ATOM DI MAN I BANDA ACEH TAHUN PELAJARAN 2019/2020 - Ruhaibah Ruhaibah (UIN AR-RANIRY, 2020)
Research about the implementation of the learning model of teams games tournament in studying atomic structures has been carried out. The purpose of this study was to increase student interest in atomic structure by using the learning model of teams games tournament. The subjects of this study were students of Class X Science 1 at MAN 1 Banda Aceh with a total of 30 students. This research;was a classroom action research which conducted in 2 cycles.The results showed that students mastery learning increased from 56.67% at meeting 1 to 60.00% at meeting 2 in cycle I. Student learning completeness increased from 80.00% at meeting 1 to 90.00% at meeting 2 in the cycle II. Based on the results of this study note that the application of the learning model of teams games tournamentcan increase student learning interest.